In vitro release of ketoprofen from proprietary and extemporaneously manufactured gels - Tettey-Amlalo, Ralph Nii Okai (Rhodes University, Faculty of Pharmacy, Pharmacy, 2005)
Ketoprofen is a potent non-steroidal anti-inflammatory drug which is used for the treatment of rheumatoid arthritis. The oral administration of ketoprofen can cause gastric irritation and adverse renal effects. Transdermal delivery of the drug can bypass gastrointestinal disturbances and provide relatively consistent drug concentrations at the site of administration. The release of ketoprofen from proprietary gel products from three different countries was evaluated by comparing the in vitro release profiles. Twenty extemporaneously prepared ketoprofen gel formulations using Carbopol® polymers were manufactured. The effect of polymer, drug concentration, pH and solvent systems on the in vitro release of ketoprofen from these formulations were investigated. The gels were evaluated for drug content and pH. The release of the drug from all the formulations obeyed the Higuchi principle. Two static FDA approved diffusion cells, namely the modified Franz diffusion cell and the European Pharmacopoeia diffusion cell, were compared by measuring the in vitro release rate of ketoprofen from all the gel formulations through a synthetic silicone membrane. High-performance liquid chromatography and ultraviolet spectrophotometric analytical techniques were both used for the analysis of ketoprofen. The validated methods were employed for the determination of ketoprofen in the sample solutions taken from the receptor fluid. Two of the three proprietary products registered under the same manufacturing license exhibited similar results whereas the third product differed significantly. Among the variables investigated, the vehicle pH and solvent composition were found have the most significant effect on the in vitro release of ketoprofen from Carbopol® polymers. The different grades of Carbopol® polymers showed statistically significantly different release kinetics with respect to lag time. When evaluating the proprietary products, both the modified Franz diffusion cell and the European Pharmacopoeia diffusion cell were deemed adequate although higher profiles were generally obtained from the European Pharmacopoeia diffusion cells. Smoother diffusion profiles were obtained from samples analysed by high-performance liquid chromatography than by ultraviolet spectrophotometry in both diffusion cells. Sample solutions taken from Franz diffusion cells and analysed by ultraviolet spectrophotometry also produced smooth diffusion profiles. Erratic and higher diffusion profiles were observed with samples taken from the European Pharmacopoeia diffusion cell and analysed by ultraviolet spectrophotometry. The choice of diffusion cells and analytical procedure in product development must be weighed against the relatively poor reproducibility as observed with the European Pharmacopoeia diffusion cell.
Keywords: Transdermal medication; Drug delivery systems; High performance liquid chromatography; Nonsteroidal anti-inflammatory agents; Rheumatoid arthritis -- Treatment